2019
DOI: 10.1002/ppul.24466
|View full text |Cite
|
Sign up to set email alerts
|

Nasal continuous positive airway pressure (NCPAP) or noninvasive neurally adjusted ventilatory assist (NIV‐NAVA) for preterm infants with respiratory distress after birth: A randomized controlled trial

Abstract: Objectives To compare rates of treatment failure between the use of nasal continuous positive airway pressure (NCPAP) and noninvasive neurally adjusted ventilatory assist (NIV‐NAVA) in infants with respiratory distress after birth. Methods A randomized, unblinded, double‐center trial was conducted in infants with birth weights (BWs) less than or equal to 1500 g and respiratory distress receiving noninvasive respiratory support for less than or equal to 48 hours of life; some infants were initially treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…Two recent randomized controlled studies comparing NIV‐NAVA with nasal CPAP during the early stages of RDS in moderately preterm infants, did not show any benefit in avoiding and/or time to intubation 57,58 (Table 4). Even though no difference was observed between NIV‐NAVA and nCPAP with respect to need of intubation in both these studies (35 vs. 50%, Kallio et al; 20.3 vs. 15.6%, Yagui et al), a longer duration of mechanical ventilation in the NIV‐NAVA group was reported in the study by Kallio et al, whereas a shorter duration could be observed by Yagui et al, possibly explained by surfactant being administered non‐invasively and earlier in the latter study but contradicted by the fact that NIV‐NAVA combined with early surfactant did not result in later intubation compared to nasal CPAP with early surfactant in that study 57,58 (Table 4). Using NIV‐NAVA after extubation seems more promising where two small retrospective studies observed more successful weaning with NIV‐NAVA than nCPAP, measured as failure within 72 h of extubation 59,60 .…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 96%
“…Two recent randomized controlled studies comparing NIV‐NAVA with nasal CPAP during the early stages of RDS in moderately preterm infants, did not show any benefit in avoiding and/or time to intubation 57,58 (Table 4). Even though no difference was observed between NIV‐NAVA and nCPAP with respect to need of intubation in both these studies (35 vs. 50%, Kallio et al; 20.3 vs. 15.6%, Yagui et al), a longer duration of mechanical ventilation in the NIV‐NAVA group was reported in the study by Kallio et al, whereas a shorter duration could be observed by Yagui et al, possibly explained by surfactant being administered non‐invasively and earlier in the latter study but contradicted by the fact that NIV‐NAVA combined with early surfactant did not result in later intubation compared to nasal CPAP with early surfactant in that study 57,58 (Table 4). Using NIV‐NAVA after extubation seems more promising where two small retrospective studies observed more successful weaning with NIV‐NAVA than nCPAP, measured as failure within 72 h of extubation 59,60 .…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 96%
“…This ability to synchronize with the patients' inspiratory efforts allows for decreased work of breathing, improved gas exchange, and earlier extubation [80,81]. Yagui et al conducted a RCT (n = 123) comparing NIV-NAVA vs. NCPAP as the primary support in infants with BW <1500 g. There was no difference noted in the primary outcome of need for intubation prior to 72 hours of life, or for the secondary outcome of BPD, between the two groups [82]. Other small RCTs have shown that NIV-NAVA is as effective as NCPAP in preventing extubation failure, but large RCTs studying the outcome of BPD in extremely preterm infants are needed before NIV-NAVA can be routinely recommended [83][84][85][86][87].…”
Section: Non-invasive Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…Stein et al in a retrospective study reported that in preterm infants managed on NAVA mode maintained better blood (89). Studies using NIV-NAVA mode in extremely preterm infants are limited with some of the recent studies showing promising results (Table 6) (16,(90)(91)(92)(93)(94)(95). Larger trials are needed to determine if NIV-NAVA is a better mode to provide sNIPPV to prevent BPD.…”
Section: Use Of Niv Nava In Nicumentioning
confidence: 99%